1983
DOI: 10.2527/jas1983.564952x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Calcium and Zinc Levels on Weight Gain and Blood and Tissue Mineral Concentrations of Growing Columbia- and Suffolk-Sired Lambs

Abstract: One hundred and sixty Columbia- and Suffolk-cross intact male and female growing lambs (8 wk of age) were used in an 84-d feeding trial to determine the effect of two levels dietary Ca and Zn on weight gain, feed utilization and several blood and tissue traits. Two levels of Ca (.5 and .8%) and two levels of Zn (20 and 100 ppm) were fed in a 2 X 2 factorial arrangement of dietary treatments. There was no effect of diet on performance or on blood traits. Columbia lambs had heavier fleeces at slaughter than Suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Findings regarding the consequences of increasing dietary calcium on the zinc availability in lambs are controversial. At low calcium levels, an influence of calcium on zinc availability was not found (5 to 8 g Ca/kg; Pond, 1983), while at even lower calcium levels serum zinc concentration was depressed with increasing calcium (2.5 to 5 g Ca/kg; Perry et al, 1968).…”
Section: Calciummentioning
confidence: 97%
“…Findings regarding the consequences of increasing dietary calcium on the zinc availability in lambs are controversial. At low calcium levels, an influence of calcium on zinc availability was not found (5 to 8 g Ca/kg; Pond, 1983), while at even lower calcium levels serum zinc concentration was depressed with increasing calcium (2.5 to 5 g Ca/kg; Perry et al, 1968).…”
Section: Calciummentioning
confidence: 97%
“…The average daily gains for lambs during rearing period were similar -about 250 g/day. According to available literature it could be stated that the zinc level in the rations had no influence on the live body mass gain or feed consumption (Pond 1983). The zinc deprivation or inadequate balance only could lead to loss of appetite and decrease of body mass gain which are result of insufficient zinc amounts for normal growth and development (Suttle 2010).…”
Section: Discussionmentioning
confidence: 99%
“…() showed that a diet containing 18 mg Zn/kg diet dry matter (DM) did not support maximal live weight gains in lambs fed a purified diet. Pond () concluded that a Zn level of 19–26 mg/kg DM would be adequate for the growth of lambs. The recommended minimum requirements are 20 mg Zn/kg DM for growth and 33 mg Zn/kg DM for the maintenance of normal reproductive functions in female lambs (NRC, ).…”
Section: Introductionmentioning
confidence: 99%